1998
DOI: 10.1007/pl00001806
|View full text |Cite
|
Sign up to set email alerts
|

Volatiles from the bark of trembling aspen, Populus tremuloides Michx. (Salicaceae) disrupt secondary attraction by the mountain pine beetle, Dendroctonus ponderosae Hopkins (Coleoptera: Scolytidae)

Abstract: Coupled gas chromatographic-electroantennographic detection (GC-EAD) analysis of the Porapak Q-captured volatiles from the bark of trembling aspen, Populus tremuloides Michx., revealed four compounds that consistently elicited antennal responses by mountain pine beetles (MPBs), Dendroctonus ponderosae Hopkins. One of these, 1-hexanol, disrupted the capture of MPBs in multiple-funnel traps baited with the aggregation pheromones trans-verbenol and exo-brevicomin and the host kairomone myrcene, a blend of semioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
106
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(112 citation statements)
references
References 27 publications
(31 reference statements)
6
106
0
Order By: Relevance
“…The stronger disruption caused by binary blends might be due to either additive or synergistic effects between different NHV/Vn signals . Several studies in North America suggested that the inhibitory effect of nonhost volatiles in blends was redundant or additive, rather than synergistic (Dickens et al, 1992a,b;Borden et al, 1998;Huber et al, 2000a;Poland & Haack, 2000). It should be noted that the NHV blend components (or signals) in the present study and in the North American tests were released individually from dispensers, therefore the total release rates for NHV/ Vn blends were several times higher than those of individual components, depending on the number of compounds or signals in the mixtures and the release rate of each individual compound or signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stronger disruption caused by binary blends might be due to either additive or synergistic effects between different NHV/Vn signals . Several studies in North America suggested that the inhibitory effect of nonhost volatiles in blends was redundant or additive, rather than synergistic (Dickens et al, 1992a,b;Borden et al, 1998;Huber et al, 2000a;Poland & Haack, 2000). It should be noted that the NHV blend components (or signals) in the present study and in the North American tests were released individually from dispensers, therefore the total release rates for NHV/ Vn blends were several times higher than those of individual components, depending on the number of compounds or signals in the mixtures and the release rate of each individual compound or signal.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the key decisions that bark beetles must make during the process of host selection (Borden, 1997;Schlyter & Birgersson, 1999) reveals that the following negative signals may be exploited in potential tactics for control of conifer bark beetles: (i) volatiles indicating the unsuitable host trees, such as verbenone (Vn) from host trees fully colonized by conspecific species, 4-allylanisole and monoterpenes from resistant hosts (Hayne et al, 1994;Byers et al, 2000;Erbilgin & Raffa, 2000), and other synomones from heterospecific bark beetles (Byers, 1995;Borden, 1997); (ii) specific bark volatiles signalling the nonhost angiosperm species (Borden et al, 1998;Schlyter & Birgersson, 1999;Huber, 2001;; or (iii) common green leaf volatiles (GLVs), especially the C 6 -alcohols emitted at high levels from leaves (and to a less extent from bark) of angiosperm trees/plants representing the nonhost habitats (Dickens et al, 1991(Dickens et al, , 1992aHuber, 2001;). Due to the inconsistent effects of Vn and 4-allylanisole, and the expensiveness of heterospecific synomones (Borden, 1997), recent studies have focused on inexpensive GLVs and other nonhost volatiles (NHVs) from the intact angiosperm trees.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, current bark beetle management focuses on exploiting semiochemical signals that interrupt host selection by bark beetles [3,16]. It would be adaptive for coniferinhabiting bark beetles to recognize and avoid general volatile compounds that are commonly found in a wide variety of nonhost deciduous and herbaceous volatiles rather than recognizing precise tree-specific volatiles for each non-host species [4]. In turn, we can make use of these properties to develop new management tools for controlling bark beetles.…”
Section: Discussionmentioning
confidence: 99%
“…Paine and Hanlon (1991) reported that verbenone disrupts the response of D. valens to traps baited with exo-brevicomin, frontalin, and myrcene [12]. In combining two or three types (habitat, species, and individual tree level) of negative stimuli, we may create an unnatural message indicative of a conspecific population that has mistakenly mass attacked an unsuitable and potentially lethal non-host habitat or species, and may be strong enough to deter bark beetles from entering treated areas [4,29].…”
Section: Discussionmentioning
confidence: 99%
“…Other less disruptive green leaf alcohols were 1-hexanol and (Z)-2-hexen-1-ol. Using coupled gas chromatographic-electronantennographic detection analysis (GC-EAD), Borden et al (1998) found four antennally-active compounds, 1-hexanol, benzaldehyde, benzyl alcohol and nonanal in the bark volatiles of trembling aspen, Populus tremuloides Michx. When tested alone and in all possible binary, ternary and quarternary combinations, they disrupted responses by D. ponderosae to pheromone-baited traps in a redundant and additive manner, and all four together were competitive with verbenone in reducing attack density on pheromone-baited lodgepole pines.…”
Section: Introductionmentioning
confidence: 99%